Day-to-day life with a rare congenital heart disease. (2nd February 2019) - Phillips, Hannah
Abstract : In February 2018, we heard the story of a young person with a rare congenital heart disease and her struggle during her transition to adult cardiac care. In this issue, Hannah Phillips returns with a quarterly column to update us about aspects of her day-to-day life with her condition